Assessment of the Neutrophil Lymphocyte Ratio and Mean Platelet Volume in Pregnancy - Rendy Singgih; Yohanes Firmansyah (HM Publisher, 2021)
Abstract Introduction: Hypertension in pregnancy is a common complication that affects maternal and fetal morbidity and mortality. Comprehensive handling is needed to overcome the incidence of hypertension in pregnancy so that it does not get worse. The use of inflammatory markers is widely used as a predictor of the incidence of hypertension in pregnancy, especially preeclampsia. Neutrophil-lymphocyte ratio (NLR) and mean platelet volume (MPV) values are believed to predict the incidence of hypertension in pregnancy. Aim of study: The purpose of this study was to determine the ability of both the NLR and MPV values to predict the incidence of hypertension in pregnancy. Methods: This research is an analytic observational study using secondary data from medical records. The data were taken from the Cimacan Regional Hospital from January to December 2019. The variables were then tested statistically to see the difference in the mean. If there are significant results, the predictor's ability will be tested again with the ROC curve test. Results: The results of statistical tests between the normotensive pregnancy group and pregnancy with hypertension showed that the mean difference was significant in the NLR variable with P-value of 0.004 and MPV with a P-value of 0.005. Then the NLR and MPV values were tested again by the ROC Curve method. The AUC results on the NLR variable (AUC: 0.562 / p-value: 0.022) and MPV (AUC: 0.560 / p-value: 0.022). Conclusion: Although NLR and MPV had differences mean between the two groups, their ability to predict pregnancy with hypertension was very low. Keywords: Pregnancy; Hypertension; Preeclampsia; NLR; MPV.